Odpornost bakterij, ki smo jih osamili pri varovancih domov za ostarele - Ribič, Helena (Zdravstveno varstvo, 2003)
Background: The frequency of infections among nursing home residents is high. Many of these infections are caused by antibiotic-resistant bacteria and treating them represents an ever-increasing problem. The authors present the most frequently isolated bacterial species and their antibiotic sensitivity rates. The strains studied were isolated from specimens taken from nursing home residents in the Ljubljana region. Methods: In this retrospective study, bacterial strains, isolated from wounds and ulcers (196 strains) and from urine samples (555 strains), were analysed. Strain isolation and antibiotic sensitivity tests were done as part of the routine work of the microbiologicallaboratory of the national Institute of Public Health between January 2000 and December 2002. Results: Among bacterial strains isolated fromurine samples, 12% of strains of enterobacteria were sensitive to ampicillin, 35% to co-amoxiclav, 32% to co-trimoxazole, 73% to gentamicin and 41% to norfloxacin; 51% of Pseudomonas aeruginosa strains were sensitive to gentamicin and 22 % to norfloxacin; 90 % of enterococci were sensitive to ampicillin, 41% to gentamicin and 7% to norfloxacin; all strains of Acinetobacter spp. were resistant to norfloxacin and 28% of strains were sensitive to gentamicin. Among strains recovered from wounds and ulcers; 33% of enterobacteria were sensitive to ampicillin, 45% to co-amoxiclav 53% to co-trimoxazole, 71% to ciprofloxacin and 75% to gentamicin. Sixty-six percent of P. aeruginosa strains were sensitive to gentamicin, 57% to ciprofloxacin and 91% to ceftazidime. All strains of Acinetobacter spp. were sensitive to ampicillin sulbactam, 6% to ciprofloxacin and 23% to gentamicin; 29% strains of Staphylococcus aureus were resistant to methicillin (MRSA strains). Conclusions: Antibiotic-resistant and multiply resistant bacteria are frequently isolated from nursing home residents in the Ljubljana region. The problem of antimicrobial resistance arises not only during treatment of infections, but also when a resident is transferred to a hospital or some other institution together with the resistant bacteria and their genes, which represent a threat to other patients. Resistant pathogens may also spread in the opposite direction : from hospitals to long-term care facilities. Consistent implementation of infection control measures and judicious use of antibiotics are required to prevent the emergence and spread of antibiotic-resistant bacteria. Microbiological surveillance is necessary to monitor microbial resistance patterns.
Keywords: antibiotic; antibiotiki; bacteria; bakterije; cepivo; cepljenje; domovi za stare ljudi; odpornost